Consumer Moral Leadership (In Factis Pax: Journal of Peace Education and Social Justice, 2020)
Despite conceptualizations of moral leadership, the literature is silent on consumer moral leadership proposed herein as a new intellectual construct. This conceptual paper reframes consumers as marketplace leaders grounded in a moral imperative. An overview of the moral leadership construct is provided from which sprang a collection of genitor constructs integrated into a new understanding of moral leadership in the consumer context: moral intelligence, discipline, integrity, courage, self-transcendence, intensity, and authority. Reasoning and argumentation strove to convince readers of the conceptual merit of the consumer moral leadership construct, which is, as yet, abstract anticipating heoretical verification.
Keywords: consumer moral leadership; moral leadership; morality; moral efficacy; ethical and moral consumerism